Mekanisme Dan Keuntungan Tabungan Prioritas yang Ditawarkan PT Bank Sumut Syariah - Nasution, Sakinah Jahrani; Lubis, Herlina; Yanti, Nursantri (Universitas Muhammadiyah Metro, 2022)
This research aims to find out how the mechanism and benefits savings priority offered PT Bank Syariah Bringjend Ktamso. The method used in this research is to use a qualitative approach with a descriptive method. Through the descriptive method, data is collected, organized, divided, analyzed, then disintegrated so that a clear picture and direction of the problem is explained. Location of research on PT. Bank Sumut Syariah KCP Bringjend Katamso. The technique used in this research is by way of direct interview with the Bank's employees, who are in charge of Customer Service, Operational, and Documentation. As for kendala to be the customer priority of PT. Bank Sumut Syariah KCP Kisaran is the requirements set forth in order to provide cash minimum Rp. 200 juta.And not many people in that area know what are the benefits they get by becoming priority customers of PT. The Bank Sumut Syariah.